The effect of corporate philanthropy on consumer behavior: Open innovation in the operating mechanism - Ufera Idrees; Hira Aftab; Hamza Ahmad Qureshi; Mário Nuno Mata; José Moleiro Martins; Pedro Neves Mata; Jéssica Nunes Martins (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The aim of this study was to highlight the effect of corporate philanthropy (CP) on consumer patronage behavior. For this purpose, reciprocity was taken as the key mechanism which determines consumers' willingness to participate in and buy goods or services of a company performing philanthropic activities. The moderating effect of trust and vicarious licensing was also studied. Considering the importance of CP to society and its residents, it is essential to recognize its effect on consumer patronage behavior. To accomplish this objective, data were collected from 340 respondents via a questionnaire. The results of this research revealed that reciprocity shows a statistically significantly positive association with both participation intention (R = 0.729, R2 = 0.531, p = 0.000, b = 0.740) and purchasing intention (R = 0.71, R2 = 0.534, p = 0.000, b = 0.878). Similarly, trust strengthens the relationship of reciprocity with both participation intention (b = 0.250) and purchasing intention (b = 0.310). However, vicarious licensing weakens the relationship of reciprocity with both participation intention (b = -0.175) and purchasing intention (b = -0.187). The mediation effect of participation intention was also examined in this study. The results of this research will contribute to the benefit of society, since philanthropy plays a vital role in society's progress. The greater response of consumers towards companies performing philanthropic activities justifies the importance of CP.
Keywords: 650; corporate philanthropy; participation intention; purchasing intention; reciprocity; trust; vicarious licensing